ESBL DETERMINATION AND ANTIBACTERIAL DRUG RESISTANCE PATTERN OF KLEBSIELLA PNEUMONIAE AMONGST PATIENTS AT PIMS ISLAMABAD - Khan, Jafar; Naz, Noor; AbdEl-Salam, Naser M.; Tabassum, Nayab Anum; Hussain, Hidayat; Ullah, Riaz (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: A number of life threatening infections due to various bacterial pathogens are major cause of death in Pakistan. In a situation likethe other developing countries, there is a general increase in the drug resistance due to the irrational use of the antibiotics. The presentstudy was carried out to evaluate the prevalence and development of resistance in Klebsiella pneumoniae against commonly usedantibiotics.Methods and Materials: A total of 200 samples from different wards of the hospitals were received by the pathology laboratory ofPakistan Institute of Medical Sciences, Islamabad, which comprised of urine 65, blood 50 and other miscellaneous samples fromvarious sources. Klebsiella pneumoniae was isolated and characterized using morphological, cultural, and biochemical methods and were furtherconfirmed by using commercially available API 20E kit. The isolates were subjected to culture sensitivity test using Kirby Bauer discdiffusion method.Results: The organism was found to be the most prevalent Gram-negative bacilli. K. pneumoniae showed highest resistance against coamoxiclavand cephalosporins.Conclusion: The study revealed that ESBL producing strains were resistant to most of the beta-lactam antibiotics. This trend thereforehas become a significant problem and can be controlled with continued surveillance or monitoring for rationally improved antibioticsusage, in order to prevent the drug resistance and re-emergence of infection.